2003
DOI: 10.1051/rnd:2003022
|View full text |Cite
|
Sign up to set email alerts
|

Determination by echography of uterine changes around puberty in gilts and evaluationof a diagnosis of puberty

Abstract: -Three experiments were carried out to evaluate the use of ultrasonography in assessing the onset of puberty in gilts. In experiment 1, gilts (n = 17) were scanned 3 times per week beginning at 133 and continuing until 187 days of age. The ultrasonic appearance of the uterus was described, quantified and compared with the reproductive status observed at slaughter. The quantification of the pictures showed a different correlation in time for infantile, impubertal, prepubertal and pubertal stages. For pubertal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
1
12
0
2
Order By: Relevance
“…In humans, different stages of puberty have been described based on morphological changes of secondary sexual characters (Marshall & Tanner, , ) and two‐dimensional ultrasonographic changes of the reproductive tract (Ivarsson, Nilsson, & Persson, ; Battaglia et al, ; Badouraki, Christoforidis, Economou, Dimitriadis, & Katzos, ). In domestic species, it has been reported that the ultrasonographic appearance of the ovaries facilitates the diagnosis of sexual maturity in prepubertal and pubertal cows (Perry & Cushman, ) and gilts (Martinat‐Botté et al, ; Kauffold, Rautenberg, Richter, Waehner, & Sobiraj, ).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, different stages of puberty have been described based on morphological changes of secondary sexual characters (Marshall & Tanner, , ) and two‐dimensional ultrasonographic changes of the reproductive tract (Ivarsson, Nilsson, & Persson, ; Battaglia et al, ; Badouraki, Christoforidis, Economou, Dimitriadis, & Katzos, ). In domestic species, it has been reported that the ultrasonographic appearance of the ovaries facilitates the diagnosis of sexual maturity in prepubertal and pubertal cows (Perry & Cushman, ) and gilts (Martinat‐Botté et al, ; Kauffold, Rautenberg, Richter, Waehner, & Sobiraj, ).…”
Section: Introductionmentioning
confidence: 99%
“…Un contrôle échographique de la taille et de l'aspect de l'utérus permet de différencier les femelles impubères (images sombres et homogènes) et celles pubères (images contrastées avec coupes utérines visibles ; figures 4 et 5). Le changement des images est brutal, 2 à 9 j avant la puberté (Martinat-Botté et al 2003). La technique peut être mise en oeuvre en élevage avec une exactitude de 97% (Martinat-Botté et…”
Section: / Oestrus Ovulation Et Parturition 21 / Détection Et Variaunclassified
“…A contrario, l'échographie est maintenant le seul outil utilisé en routine par les éleveurs pour détecter la gestation des truies et ceci dès 20 j. La littérature, abondante sur ce point, est unanime pour reconnaître la fiabilité de ce diagnostic (97% d'exactitude) qui permet en outre de réduire les temps improductifs(Martinat-Botté et al 1998, Kauffold et Althouse 2007.…”
unclassified
“…In pigs, puberty is defined as the emergence of the first estrous and follicular maturation [26], and early puberty is selected to shorten the generation interval [27, 28]. Moreover, pigs are the valuable biomedical and pubertal model due to the similar processes in follicular maturation [9, 10] and pubertal transition to humans [29, 30].…”
Section: Introductionmentioning
confidence: 99%